2012
DOI: 10.1002/jcb.24387
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid and the transcription factor MafB act together and differentially to regulate aggrecan and matrix metalloproteinase gene expression in neonatal chondrocytes

Abstract: Vitamin A (VA) and its active form, retinoic acid (RA), are regulators of skeletal development and chondrogenesis. MafB, a transcription factor, has been identified as an important mediator in monocyte and osteoclast differentiation. However, the presence and function of MafB in chondrocytes is not clear. In this study, MafB gene expression was regulated by both the VA status of the mother (VA-marginal, adequate, and supplemented diets) and by direct oral supplementation of the neonates with VARA (VA mixed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Potential pan‐RARs were designed based on BMS 493 . In chondrocytes it was shown to block completely the RA‐induced increase in MafB expression . In the study of Zhang and Ross the RA was used in a concentration of 20 n m while the inhibitor was used in a concentration of 1 μ m .…”
Section: Methodsmentioning
confidence: 99%
“…Potential pan‐RARs were designed based on BMS 493 . In chondrocytes it was shown to block completely the RA‐induced increase in MafB expression . In the study of Zhang and Ross the RA was used in a concentration of 20 n m while the inhibitor was used in a concentration of 1 μ m .…”
Section: Methodsmentioning
confidence: 99%
“…MAFB is a transcription factor of the large MAF subfamily (MAFA, cMAF, MAFB, NRL) that binds to a specific DNA element (MARE); heterodimerizes with cMAF, JUN, and FOS (17)(18)(19); and associates and functionally inhibits MYB (19), MITF, and NFATc1 (20). MAFB controls lens development (21), lymphangiogenesis (22), pancreatic a and b cell differentiation (23,24), skin cell differentiation (25), chondrocyte matrix formation and development (26), and podocyte generation (27)(28)(29)(30), and also regulates type I IFN production through recruitment of coactivators to IFN regulatory factor 3 (31). Within the murine myeloid lineage, MafB is preferentially expressed in most tissue-resident macrophages, whose specific enhancers contain an overrepresentation of MARE sequences (32).…”
mentioning
confidence: 99%
“…Zhang et al reported that retinoic acid-induced MMP-3 and MMP-13 gene expression was attenuated in MafB-knockdown chondrocytes 36. MMP-3 and MMP-13 are induced in terminally differentiated chondrocytes, and MMP-12 is produced by differentiated macrophages 37.…”
Section: Discussionmentioning
confidence: 99%